(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
Spatial perception abilities are necessary in STEM field, so we have been monitoring them and adapting our teaching methods to student needs. We digitized MRT and MCT tests and created new multimedia teaching materials for e-courses. Low spatial perception is the biggest problem in solving geometric tasks in space. This affects all technical courses, especially geometric ones. Spatial abilities develop with exercise. This paper analyzes this problem, gives an overview of MRT and MCT test results and describes the use of digital teaching materials.